2014
DOI: 10.3109/14992027.2014.981305
|View full text |Cite
|
Sign up to set email alerts
|

Does tinnitus, hearing asymmetry, or hearing loss predispose to occupational injury risk?

Abstract: Objective To determine the relative contributions of tinnitus, asymmetrical hearing loss, low frequency hearing loss (pure tone average of .5, 1, 2, 3 kHz, PTA.5123), or high frequency hearing loss (pure tone average of 4, 6 kHz, PTA46), to acute injury risk among a cohort of production and maintenance workers at six aluminum manufacturing plants, adjusting for ambient noise exposure and other recognized predictors of injury risk. Design and Study Sample This retrospective analysis considered 9,920 workers e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The results of this study also indicated that neuroses, arterial hypertension, eye diseases, hearing disturbances, and overweight and obesity were significantly more present in the group of workers who had workplace injuries, compared with the workers who had not, which was in accordance with the literature data (24,25,26).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study also indicated that neuroses, arterial hypertension, eye diseases, hearing disturbances, and overweight and obesity were significantly more present in the group of workers who had workplace injuries, compared with the workers who had not, which was in accordance with the literature data (24,25,26).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the presence of tinnitus and/or NIHL has implications for worker safety, as they are often associated with impaired speech discrimination and a higher risk of accidents in the workplace. 2 , 22 , 114 , 115 …”
Section: Discussionmentioning
confidence: 99%
“…This may be because noise blocks communication with co-workers and masks warning signals at the fire ground ( 15 16 ). If workers have hearing defects, the risk of occupational injury may be increased ( 17 ). High frequency noise can be caused by sirens while driving emergency cars or fire trucks, when handling various equipment such as water pumps and saws or with sudden explosions at the fire ground ( 18 ).…”
Section: Discussionmentioning
confidence: 99%